Uwagi nad dziejami wsi Brodnia koło Sieradza (do początków XVII wieku) - Zajączkowski, Stanislaw Marian (Acta Universitatis Lodziensis. Folia Archaeologica, 1994)
The object of this paper is to outline the history of the village of Brodnia to the early 17th century. The village, now situated in the commune of Pęczniew, in the Sieradz province, was in the past (to the time of partitions) in the district and province of Sieradz. As a royal property it belonged to the Sieradz district (starostwo) and later to the so-called tenure of Szadek. The origins of Brodnia are not known though they may go back to the 11th century of even to earlier times. It was a prince’s village. Between 1288 and 1298 it was given by Władysław Łokietek (the Short) to Stoigniew, castellan of Ruda, yet in 1298 the King exchanged it for another of this properties. In the early 14th century a farm was founded there and about the middle of that century a tower was built on the mound within the farm. It served as a centre of farm administration and also as a residence of the king during his visits to Brodnia. In the times of Władysław Jagiełło courts in curia were held there around the Palm Sunday. Written sources mention 18 visits of this King to Brodnia, linked with his habit of touring the country. This practice was abandoned by later kings; only one of them, Casimir Jagiellończyk, was once at Brodnia in 1450. The royal visits to Brodnia doubtless contributed to its economic development. When the royal tours of the country were discontinued, the tower on mound ceased to perform its function and was abandoned in the mid-15th century and destroyed by fire in the middle of the next century. In the 14th century Brodnia was probably founded under the German law. The foundation documents is not known. That Brodnia must have been in the possession of that law is attested by mentions of the 16th-17th centuries referring to the village administrators (scultetus) or to fields that belonged to them. About the middle of the 16th century their office was abolished at Brodnia and the endowed lands (2 lanei) were incorporated into the farm land. Farming was the basic occupation of the inhabitants of Brodnia who, however, pursued other occupations such ad crafts, fishing and bee-keeping as well. As testified by the inspection of crown lands in 1564-1565, their lot was not too hard. Though they paid money rent and rent in kind (cereals, hens, cheese, eggs, butter, etc.), their villein service was not an arduous one. Yet the inspection of 1628-1632 shows that by the end of the 16th and in the early 17th century the villein service became dominant. At that time feudal opression grew in intensity. Since Brodnia was a fairly well developed village, it brought profit to kings. For this reason, certain suras bequeathed by our monarchs to the magnates were drawn on the village profits; the village was also given as pledge for money lent. It should yet be mentioned that a small church, affiliated to the parish church at the village of Glinno, was built there probably in the 14th century. It was under the care of a curate first mentioned in 1417.